2014
DOI: 10.1073/pnas.1324037111
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the right inferior longitudinal fasciculus but no general disruption of white matter tracts in children with autism spectrum disorder

Abstract: One of the most widely cited features of the neural phenotype of autism is reduced "integrity" of long-range white matter tracts, a claim based primarily on diffusion imaging studies. However, many prior studies have small sample sizes and/or fail to address differences in data quality between those with autism spectrum disorder (ASD) and typical participants, and there is little consensus on which tracts are affected. To overcome these problems, we scanned a large sample of children with autism (n = 52) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
99
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(121 citation statements)
references
References 40 publications
(42 reference statements)
21
99
1
Order By: Relevance
“…Kirkovski et al (2015) found no differences between high functioning individuals with ASD and typical controls in white matter in major tract bundles determined by any method: fractional anisotropy (FA), mean diffusivity (MD), radial diffusivity (RD), or axial diffusivity (AD). Koldewyn et al (2014) reported finding no general impaired white matter in ASD. Lefebvre et al (2015) found no differences between 694 individuals diagnosed with ASD and typical controls in the largest white matter tract in the brain-the corpus callosum.…”
Section: Does Asd Have Neurobiological Validity?mentioning
confidence: 98%
“…Kirkovski et al (2015) found no differences between high functioning individuals with ASD and typical controls in white matter in major tract bundles determined by any method: fractional anisotropy (FA), mean diffusivity (MD), radial diffusivity (RD), or axial diffusivity (AD). Koldewyn et al (2014) reported finding no general impaired white matter in ASD. Lefebvre et al (2015) found no differences between 694 individuals diagnosed with ASD and typical controls in the largest white matter tract in the brain-the corpus callosum.…”
Section: Does Asd Have Neurobiological Validity?mentioning
confidence: 98%
“…The literature on techniques to identify and remove motion artifact is currently one of the most rapidly evolving fronts of functional connectivity MRI (e.g., (Bright and Murphy, 2013; Kundu et al, 2013; Power et al, 2014; Yan et al, 2013)), and multiple methods now exist that have evidence for removing much or nearly all motion artifact from resting state datasets. The problems caused by small movements are unfortunately not limited to functional connectivity MRI: previously unrecognized effects of small movements, capable of causing spurious group differences, have recently been reported in the structural connectivity MRI literature (e.g., (Koldewyn et al, 2014; Yendiki et al, 2013)).…”
Section: Obtaining Correlates Of Spontaneous Neural Activity With Fmrimentioning
confidence: 99%
“…Substantial emphasis has been placed on characterizing how motion‐induced artifacts affect echo‐planar imaging (EPI): both in functional MRI [fMRI; Power et al, 2014; Satterthwaite et al, 2012; Siegel et al, 2014; Van Dijk et al, 2012; Zeng et al, 2014] and diffusion weighted imaging [DWI; Koldewyn et al, 2014; Thomas et al, 2014; Yendiki et al, 2013]. There has been less focus on characterizing how spurious motion‐related biases impact high‐resolution T1‐weighted (T1w) images.…”
Section: Introductionmentioning
confidence: 99%